ANALISIS TINDAK TUTUR LOKUSI, ILOKUSI, DAN PERLOKUSI PADA FILM “PAPA MAAFIN RISA” - Tuti Hidayah; Rochmat Tri Sudrajat; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
language. When someone speaks, then there is an interlocutor who will give a response to his speech. the formulation of the problem to be conveyed is analyzing speeches and speech acts. The purpose of this study is to describe each of the utterances that contain locus, illocutionary, and percocutionary events from the character in the film "Papa Maafin Risa". This research method uses descriptive qualitative method that is describing each dialogue conveyed by the figures. the film depicts how the speech events and speech acts are conveyed, so that locus events take the form of statements from the speaker and then illocution that will have an impact on the listener such as giving promises and offers to the interlocutor and perlocutionwhich will have an impact on the behavior of the speaker and the interlocutor.all of that will be reflected in each dialogue discussed in the three speech events.